Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

7.3: Integrability Conditions

  • Page ID
    22680
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \) \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\) \(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)

    Proposition \(\PageIndex{1}\)

    If \(a<b\) and \(f:[a, b] \rightarrow \mathbb{R}\) is monotonic, then \(f\) is integrable on \([a, b]\).

    Proof

    Suppose \(f\) is nondecreasing. Given \(\epsilon>0,\) let \(n \in Z^{+}\) be large enough that

    \[\frac{(f(b)-f(a))(b-a)}{n}<\epsilon .\]

    For \(i=0,1, \ldots, n,\) let

    \[x_{i}=a+\frac{(b-a) i}{n}.\]

    Let \(P=\left\{x_{0}, x_{1}, \ldots, x_{n}\right\} .\) Then

    \[\begin{aligned} U(f, P)-L(f, P) &=\sum_{i=1}^{n} f\left(x_{i}\right)\left(x_{i}-x_{i-1}\right)-\sum_{i=1}^{n} f\left(x_{i-1}\right)\left(x_{i}-x_{i-1}\right) \\ &=\sum_{i=1}^{n}\left(f\left(x_{i}\right)-f\left(x_{i-1}\right)\right) \frac{b-a}{n} \\ &=\frac{b-a}{n}\left(\left(f\left(x_{1}\right)-f\left(x_{0}\right)\right)+\left(f\left(x_{2}\right)-f\left(x_{1}\right)\right)+\cdots\right.\\ &\left.\quad+\left(f\left(x_{n-1}\right)-f\left(x_{n-2}\right)\right)+\left(f\left(x_{n}\right)-f\left(x_{n-1}\right)\right)\right) \\ &=\frac{b-a}{n}(f(b)-f(a)) \\ &<\epsilon . \end{aligned}\]

    Hence \(f\) is integrable on \([a, b]\). \(\quad\) Q.E.D.

    Example \(\PageIndex{1}\)

    Let \(\varphi: \mathbb{Q} \cap[0,1] \rightarrow \mathbb{Z}^{+}\) be a one-to-one correspondence. Define \(f:[0,1] \rightarrow \mathbb{R}\) by

    \[f(x)=\sum_{q \in \underset{q \leq x}{\mathbb{Q} \cap [0,1]}} \frac{1}{2^{\varphi(q)}.}\]

    Then \(f\) is increasing on \([0,1],\) and hence integrable on \([0,1]\).

    Proposition \(\PageIndex{2}\)

    If \(a<b\) and \(f:[a, b] \rightarrow \mathbb{R}\) is continuous, then \(f\) is integrable on \([a, b]\).

    Proof

    Given \(\epsilon>0,\) let

    \[\gamma=\frac{\epsilon}{b-a}.\]

    Since \(f\) is uniformly continuous on \([a, b],\) we may choose \(\delta>0\) such that

    \[|f(x)-f(y)|<\gamma\]

    whenever \(|x-y|<\delta .\) Let \(P=\left\{x_{0}, x_{1}, \ldots, x_{n}\right\}\) be a partition with

    \[\sup \left\{\left|x_{i}-x_{i-1}\right|: i=1,2, \ldots, n\right\}<\delta .\]

    If, for \(i=1,2, \dots, n\),

    \[m_{i}=\inf \left\{f(x): x_{i-1} \leq x \leq x_{i}\right\}\]

    and

    \[M_{i}=\sup \left\{f(x): x_{i-1} \leq x \leq x_{i}\right\},\]

    then \(M_{i}-m_{i}<\gamma .\) Hence

    \[\begin{aligned} U(f, P)-L(f, P) &=\sum_{i=1}^{n} M_{i}\left(x_{i}-x_{i-1}\right)-\sum_{i=1}^{n} m_{i}\left(x_{i}-x_{i-1}\right) \\ &=\sum_{i=1}^{n}\left(M_{i}-m_{i}\right)\left(x_{i}-x_{i-1}\right) \\ &<\gamma \sum_{i=1}^{n}\left(x_{i}-x_{i-1}\right) \\ &=\gamma(b-a) \\ &=\epsilon . \end{aligned}\]

    Thus \(f\) is integrable on \([a, b]\). \(\quad\) Q.E.D.

    Exercise \(\PageIndex{1}\)

    Suppose \(a<b, f:[a, b] \rightarrow \mathbb{R}\) is bounded, and \(c \in[a, b] .\) Show that if \(f\) is continuous on \([a, b] \backslash\{c\},\) then \(f\) is integrable on \([a, b]\).

    Exercise \(\PageIndex{2}\)

    Suppose \(a<b\) and \(f\) is continuous on \([a, b]\) with \(f(x) \geq 0\) for all \(x \in[a, b] .\) Show that if

    \[\int_{a}^{b} f=0,\]

    then \(f(x)=0\) for all \(x \in[a, b]\).

    Exercise \(\PageIndex{3}\)

    Suppose \(a<b\) and \(f\) is continuous on \([a, b] .\) For \(i=0,1, \ldots, n\), \(n \in \mathbb{Z}^{+},\) let

    \[x_{i}=a+\frac{(b-a) i}{n}\]

    and, for \(i=1,2, \ldots, n,\) let \(c_{i} \in\left[x_{i-1}, x_{i}\right] .\) Show that

    \[\int_{a}^{b} f=\lim _{n \rightarrow \infty} \frac{b-a}{n} \sum_{i=1}^{n} f\left(c_{i}\right).\]

    In the notation of Exercise \(7.3 .3,\) we call the approximation

    \[\int_{a}^{b} f \approx \frac{b-a}{n} \sum_{i=1}^{n} f\left(c_{i}\right)\]

    a right-hand rule approximation if \(c_{i}=x_{i},\) a left-hand rule approximation if \(c_{i}=x_{i-1},\) and a midpoint rule approximation if

    \[c_{i}=\frac{x_{i-1}+x_{i}}{2}.\]

    These are basic ingredients in creating numerical approximations to integrals.

    • Was this article helpful?